Rat pancreatic kallikrein mRNA: nucleotide sequence and amino acid sequence of the encoded preproenzyme. - Swift, G H (1982)
We have cloned via recombinant DNA technology the mRNA sequence for rat pancreatic preprokallikrein. Four cloned overlapping double-stranded cDNAs gave a continuous mRNA sequence of 867 nucleotides beginning within the 5'-noncoding region and extending to the poly(A) tail. The mRNA sequence reveals that pancreatic kallikrein is synthesized as a prezymogen of 265 amino acids, including a proposed secretory prepeptide of 17 amino acids and a proposed activation peptide of 11 amino acids. The activation peptide, although similar in length, is distinct from those of the other classes of pancreatic serine proteases. The amino acid sequence of the predicted active form of the enzyme is closely related to the partial sequences obtained for other kallikrein-like serine proteases including rat submaxillary gland kallikrein, pig pancreatic and submaxillary gland kallikreins, the gamma subunit of mouse nerve growth factor, and rat tonin. Key amino acid residues thought to be involved in the substrate-cleavage specificity of kallikreins are retained. Hybridization analysis showed relatively high levels of kallikrein mRNA in the rat pancreas, submaxillary and parotid glands, spleen, and kidney, indicating the active synthesis of kallikrein in these tissues.